A multicenter prospective study of 515 febrile neutropenia episodes in Argentina during a 5-year period - Parodi, Roberto Leandro (2019)
Fil: Fil: Parodi, Roberto Leandro. Universidad Nacional de Rosario. Facultad de Ciencias Médicas. Rosario; Argentina